A training model for e-readiness in e-governance. (6th April 2009) - Aggarwal, A.K.
Advances in information and communication technologies (ICT) are providing opportunities for both public and private organisations to offer e-services on the web. In the e-service environment stakeholders are customers and customer satisfaction becomes vital. E-readiness is a prerequisite for all e-services. Training has been identified as a major component for e-readiness. Unfortunately, training has been typically ignored. This paper focuses on employee training and proposes a process and a model for training employees for the e-environment. The model links four factors: job classification (roles), job requirements, training levels and training modes to e-readiness. In addition, we discuss techniques to assess training effectiveness needed for continuous improvement. This paper should be useful for countries that are planning e-readiness for e-governance or are concerned about efficiency and lack of e-participation in e-government. Instead of re-inventing the wheel, governments can use the model presented here to select training mode by matching job characteristics to the level of training requirement. We feel this is a first attempt in this direction.